Chromaticity of some Tripartite Graphs - Yin, Jun; Zhao, Haixing; Ma, Xiujuan; Li, Yalan (Discontinuity, Nonlinearity, and Complexity, 2026)
For any graph G, we use P(G, λ) to denote the the chromatic polynomial of G. Two graphs G and H are said to be equivalent, simply denoted by GH, if P(G, λ)=P(H, λ). Let [G]={H|HG}. G is said to be chromatically unique if [G]={G}. Let K(n, n, n) be the complete tripartite graph with each part vertex set having n vertice and S be an edge set of s edges in K(n, n, n). In this paper, we give some chromatically unique tripartite graphs obtained by deleting some edges from K(n, n, n) .